Polybenzimidazole-based polymeric ionic liquids (PILs): effects of `substitution asymmetry' on CO2 permeation properties - Shaligram, Sayali V.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric Ionic Liquids (PILs) are being considered as promising membrane materials for CO2 separation. Present work aims at investigating effects substitution asymmetry on imidazole moiety of two structurally different polybenzimidazoles (PBI-BuI and PBI-HFA) on physical, gas sorption and transport properties of the resulting film forming PILs possessing symmetric substitution, while keeping one of the N-substituent as methyl group. PILs were obtained with high degree of substitution. The halide anion of these PILs was exchanged with BF4-, Tf-2(N) over bar and HF (B) over bar anions. Effects of substituents, cationic backbone and type of anions on gas permeation properties of PILs using pure gases (He, H-2, N-2 and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. Combination of typical ionic liquid character (effective towards enhancing CO2 sorption) and looser chain packing (ease in gas diffusion) offered improved CO2 permeation characteristics. As an outcome, some of the PILs exhibited higher CO2 permeation than that of hydrogen, typically known as `reverse selectivity'. These asymmetrically substituted PILs enhanced not only the gas permeability, but also selectivity than their symmetrically substituted counterparts. (C) 2015 Elsevier B.V. All rights reserved.